2009
DOI: 10.1080/08860220902882741
|View full text |Cite
|
Sign up to set email alerts
|

3-Aminobenzamide, a Poly ADP Ribose Polymerase Inhibitor, Attenuates Renal Ischemia/Reperfusion Injury

Abstract: Introduction. This study was designed to investigate whether 3-amino benzamide (3-AB), a poly (ADP-ribose) polymerase (PARP) inhibitor, has a protective effect on kidney injury induced by renal ischemia/reperfusion (I/R) by decreasing oxidative and nitrosative stress on renal dysfunction and injury. Materials and Methods. Thirty-two male SpragueDawley rats were divided into four groups: sham-operated, sham-operated + 3-AB, I/R, I/R + 3-AB. Rats were given 3-AB (100 mg/kg/day ip) 14 days prior to I/R. I/R and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…[37][38][39] In our team's previous works, beneficial effects of PARP inhibition were shown in different experimental inflammatory models. [40][41][42] Therefore, it is possible that treatment with a PARP inhibitor may also attenuate renal injury in kidneys subjected to ESW.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] In our team's previous works, beneficial effects of PARP inhibition were shown in different experimental inflammatory models. [40][41][42] Therefore, it is possible that treatment with a PARP inhibitor may also attenuate renal injury in kidneys subjected to ESW.…”
Section: Discussionmentioning
confidence: 99%
“…The production of ONOO − (nitrosative stress) occurs almost instantaneously and causes the nitration of cellular proteins with subsequent loss of protein structure and function. [15,39,40] Therefore, we conclude that ONOO − is critical in renal I/R injury, and that the reduction of ONOO − may be a potential mechanism to prevent kidneys.…”
Section: Onoomentioning
confidence: 99%
“…Efficacy of treatment was assessed by tissue level of malondialdehyde (MDA) using the method of Ohkawa et al, protein carbonyl content (PCC) using the method of Levine et al, superoxide dismutase (SOD) using the method of Sun et al, and glutathione peroxidase (GPx) using the method of Paglia and Valentine. [13,30,40] Nitrate and nitrite (NO x ) levels, end products of nitric oxide degradation, were measured using the method described by Miranda et al, as we described in our previous works. [13,30] …”
Section: Biochemical Analysismentioning
confidence: 99%
“…[18][19][20] On the other hand, some studies have shown the ameliorative effects of therapeutic agents via preventing ROS production, inhibiting enzymes responsible for ROS generation, and administration of antioxidant enzymes and scavenging of ROS. [2][3][4][5][10][11][12]21 In this study, we evaluated the possible beneficial effects of NAC as a free radical scavenger antioxidant. We found that administration of NAC prior to injury showed considerable improvement in renal IRI by decreasing lipid peroxidation and increasing antioxidant enzyme activity.…”
Section: Mda (Nmol/g-protein)mentioning
confidence: 99%
“…16,31 NO and ONOO -are eventually converted to nitrite and/or nitrate. NO x has been used as an indirect but reliable indicator for NO 4,5,21 and ONOO -formation in vivo. 4,36 Therefore, the reduction of ONOO -level and increase in the scavenging of ROS activity may be a potential mechanism to protect kidneys against IRI.…”
Section: Mda (Nmol/g-protein)mentioning
confidence: 99%